Asuhan Keperawatan Postpartum Pada Ny. A Dengan Nyeri Luka Perineum Melalui Penerapan Massage Effleurage Menggunakan Minyak Zaitun Di Ruang Bougenville RSUD Raja Ahmad Tabib Tanjungpinang - Efika Efika; Komala Sari; Meily Nirnasari; Wasis Pujiati (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Postpartum perineal wounds can cause various postpartum problems, pain due to incision wounds can cause infection if not treated properly. Infection of the perineal wound can be a source of other infections in the mother, and if not treated properly, it can cause postpartum death. One of the non-pharmacological therapies to reduce pain intensity is effleurage massage using olive oil. This technique is a gentle massage with olive oil to reduce pain and provide comfort to the mother. This case study aims to provide nursing care through the application of effleurage massage with olive oil to reduce the intensity of perineal wound pain in postpartum mothers. This study uses a descriptive observational method in the form of a case study. The subject in this case is Mrs. A, 21 years old with perineal wound pain who was treated in the Baougenville room, Raja Ahmad Tabib Hospital, Tanjungpinang for 3 days on October 31 to November 2, 2024. Data were obtained from interviews, observations, physical examinations, supporting examinations, and documentation studies. The results of the study showed that the measurement of pain intensity on the first day was 6, after being given effluarge massage on the second day it decreased to 4 and on the third day it became 2. This shows that effluarge massage has a significant effect in reducing the intensity of prenieum wound pain. It is expected that nurses can carry out effluarge massage therapy to reduce the intensity of prenieum wound pain in postpartum mothers.